Recent advances on organic‐inorganic hybrid perovskite photodetectors with fast response. Issue 2 (29th May 2019) - Zhao, Yan; Li, Chenglong; Shen, Liang
Abstract: In the last decade, optoelectronic devices based on organic‐inorganic hybrid perovskite (OIHP) materials, which have unique advantages of direct bandgap, large absorption coefficient, low density of defects, long charge carrier lifetime, and diffusion length as well as solution processability, have traveled with traditional inorganic semiconductor devices. The state‐of‐the‐art OIHP photodetectors have contributed a comparable performance with Si and III‐V compound semiconductor based photodetectors. Large amount of efforts have been focused on improving sensitivity, broadening detection spectra, enlarging linear dynamic range. However, few reports emphasized the important parameter of response speed. In this review, we summarize the progress and employment of OIHP photodetectors with fast response. Based on photovoltaic and photoconductive type OIHP photodetectors, the working principle and key factors on determining response speed are systematically mentioned. Then, the research progress of response speed composed of resistance‐capacitance (RC) time constant and charge carrier transit time were discussed in detail. Subsequently, considering the intrinsic flexibility of perovskite materials, we briefly discussed the flexible photodetectors. Finally, an outlook as well as potential rules for designing fast‐response OIHP photodetectors is further proposed. Abstract : The empolyment and working principle of perovskite photodetectors with fast response speed composed of RC time and carrier transit time are systematically reviewed.